2020
DOI: 10.1029/2020jb019829
|View full text |Cite
|
Sign up to set email alerts
|

Supershear Frictional Ruptures Along Bimaterial Interfaces

Abstract: We experimentally and analytically explore supershear ruptures that are excited at the onset of frictional motion within “bimaterial interfaces,” frictional interfaces formed by contacting bodies having different elastic (or geometric) properties. Our experiments on PMMA blocks sliding on polycarbonate show that the structure, transition sequence, and range of existence of such supershear ruptures are highly dependent on their propagation direction relative to the slip direction in the softer of the two materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
3
15
0
Order By: Relevance
“…The present approach significantly extends the results of our analysis in the transonic and supersonic regimes [15,16] to the subsonic regime where all ruptures initiate. This work will allow for a more complete picture of the onset of frictional sliding between dissimilar materials and reveals a qualitatively new class of instabilities.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…The present approach significantly extends the results of our analysis in the transonic and supersonic regimes [15,16] to the subsonic regime where all ruptures initiate. This work will allow for a more complete picture of the onset of frictional sliding between dissimilar materials and reveals a qualitatively new class of instabilities.…”
Section: Introductionsupporting
confidence: 69%
“…These studies revealed that interfacial crack tip speeds in bimaterials can exceed not only the c R of the softer material but also its shear wave speed. Such 'supershear' modes were also later observed [10,16,46] in frictional bimaterial experiments. While certainly related to bimaterial frictional ruptures, it is still unclear how the two systems map to one another.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations